Electron beam transversion management on exit of magnetic gun by gradient magnetic field - Mazmanishvili, A.S.; Reshetnyak, N.G.; Romasko, V.P.; Chertishchev, I.A. (Вопросы атомной науки и техники, 2020)
The results of experimental studies and modeling calculations for controlling the transverse dimensions of an electron beam formed by a magnetron gun with a secondary emission cathode are presented. In the gun, the secondary emission process is launched by a voltage pulse with an amplitude of up to 15 kV supplied to its anode. The dependence of the radial dimensions of the electron beam on the amplitude and gradient of the magnetic field in the transport channel is investigated. It is shown that the obtained experimental results are consistent with the simulation results. The possibility of adjusting the beam diameter by varying the configuration of the magnetic field is established. The experimental results presented indicate the possibility of realizing irradiation of the outer surface of cylindrical samples placed in the region of the gradient magnetic field. Представлено результати експериментальних досліджень і моделюючих розрахунків з управління поперечними розмірами електронного пучка, що формується магнетронною гарматою з вторинно-емісійним катодом. У гарматі запуск вторинно-емісійного процесу виконується імпульсом напруги амплітудою до 15 кВ, що подається на її анод. Досліджена залежність радіальних розмірів електронного пучка від амплітуди та градієнта магнітного поля в каналі транспортування. Показано, що отримані експериментальні результати узгоджуються з результатами моделювання. Встановлена можливість регулювання діаметра пучка шляхом варіації конфігурації магнітного поля. Вказана можливість опромінювати зовнішню поверхню циліндричних зразків, що розташовані в області градієнтного магнітного поля. Представлены результаты экспериментальных исследований и моделирующих расчетов по управлению поперечными размерами электронного пучка, формируемого магнетронной пушкой с вторичноэмиссионным катодом. В пушке запуск вторично-эмиссионного процесса осуществляется импульсом напряжения амплитудой до 15 кВ, подаваемым на её анод. Исследована зависимость радиальных размеров электронного пучка от амплитуды и градиента магнитного поля в канале транспортировки. Показано, что полученные экспериментальные результаты согласуются с результатами моделирования. Установлена возможность регулировки диаметра пучка путем вариации конфигурации магнитного поля. Указана возможность облучать наружную поверхность цилиндрических образцов, помещенных в область градиентного магнитного поля.